Social inequalities in neonatal mortality and living condition - Annelise C. Gonçalves; Maria da Conceição N. Costa; Jairnilson S. Paim; Ligia Maria Vieira da Silva; José Ueleres Braga; Mauricio Barreto (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
Objective: To evaluate the association between the spatial distribution of neonatal mortality and living conditions, and to analyze trends in the social inequalities, related to this mortality, in Salvador, Bahia, Brazil, 2000 - 2006. Methods: The city's Information Zones, the unit of analysis used in this study, were grouped into strata reflecting high, intermediate, low and very low living conditions, based on a living conditions index (LCI). Neonatal mortality rates were calculated for each stratum. Spearman's correlation, linear regression and relative risks were used in the data analysis. Results: Neonatal mortality in Salvador was found to be associated with living conditions, with risks of 53, 56 and 59% greater, respectively, in the intermediate, low and very low strata, when compared to the high living conditions stratum. Only the intermediate living conditions stratum shows a significant decline in neonatal mortality (Î² = -0.93; p = 0.039). In the stratum of high living conditions, it was observed a stagnation of this mortality. Conclusions: Poorer living conditions were associated to higher risks of neonatal mortality. The slight decline in social inequalities, found in neonatal mortality, was due to a decline in the intermediate living conditions stratum. Although dependent on the access to quality healthcare services and life support technologies, a more consistent reduction in the neonatal mortality and its associated inequalities will only be achieved when broader-reaching public policies are implemented, improving the living conditions, and mainly focusing on priority groups.